Study on the Mechanism of Weakening Thick and Hard Roof by Deep-Hole Blasting in Deep Coal Mines - Zhang, Chen; Zou, Junpeng; Zhang, Xiufeng; Wang, Chao; Jiao, Yu-Yong (Frontiers in Earth Science, 2022)
In the mining process of deep coal mines with a thick and hard roof, it is easy to form a large overhanging roof and accumulate a lot of strain energy. The sudden breaking of the suspended roof may induce seisms, which seriously threaten the safety of underground miners and equipment. To reveal the mechanism of weakening the thick and hard roof by blasting in deep mining, the four times deep-hole blasting in 63upper06 panel of Dongtan coal mine are considered. Firstly, the temporal and spatial distribution of seismicity events monitored before and after blasting is investigated. Secondly, the process of deep-hole blasting is simulated using finite element and discrete element methods. After blasting, the small-energy mining-induced seismicities within 20m of the roof suddenly increase, and gradually transfer to the mined-out area and the front of the working face. Meanwhile, the high rock stratum is broken and a large amount of strain energy is released, which causes the range of fall zone enlarge a lot, and the stress in the roof decreased obviously. With the increase in the number of deep-hole blasting, the pressure relief effect becomes more obvious, and the newly developed fracture is mainly located in the low strata. Microseismic monitoring results agree with the calculated results. Besides, the rock caving steps are easily formed after deep-hole blasting, and the collapse is more sufficient. Furthermore, blasting cracks are most restrained in the vertical direction of the maximum principal stress. Moreover, the delayed blasting method is more conducive to the expansion and penetration of blasting cracks. Results show that the deep-hole blasting technology has a significant effect on weakening the roof of coal seam and preventing and controlling large-energy mining-induced seismicities.